Hypophysitis related to immune checkpoint inhibitors: An intriguing adverse event with many faces. (3rd August 2021) - Deligiorgi, Maria V; Liapi, Charis; Trafalis, Dimitrios T
ABSTRACT: Introduction: The incorporation of immune checkpoint inhibitors in the oncologists' arsenal is a milestone in cancer therapeutics, though not being devoid of toxicities. Areas covered: The present review provides a comprehensive and up-to-date overview of the immune-related hypophysitis with focus on the elusive biological background, the wide spectrum of the epidemiological profile, the varying clinical aspects, and the diagnostic and therapeutic challenges. Expert opinion: Historically considered distinctive of anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4) monoclonal antibodies (mAbs), the immune-related hypophysitis is increasingly correlated with the anti-programmed cell-death (PD) protein 1 (PD-1)/anti-PD ligand 1 (PD-L1) mAbs. The distinct phenotype of hypophysitis related to anti-PD1/anti-PD-L1 mAbs is highlighted with focus on the immune-related isolated adrenocorticotropic (ACTH) deficiency. The immune-related central diabetes insipidus is discussed as a rare aspect of anti-CTL-A4 mAbs-induced hypophysitis, recently related to anti-PD1/anti-PD-L1 mAbs as well. The present review builds on existing literature concerning immune-related hypophysitis underscoring the pending issues still to be addressed, including (i) pathogenesis; (ii) correlation with preexisting autoimmunity; (iii) predictive value; (iv) utility of high-dose glucocorticoids; and (v) establishment of evidence-based diagnostic and therapeutic protocols. Increased awareness and constant vigilance are advocated as cornerstone of a multidisciplinary approach to ensure optimal patients' care.